Innovation, intermediation, and the nature of entrepreneurship: A historical perspective. (28th January 2019) - Toms, Steven; Wilson, Nick; Wright, Mike
Abstract : Research Summary : We consider two sources of innovation, technical and financial, and examine their separate and joint impacts, through the process of financial intermediation, on the nature of entrepreneurial opportunity. These impacts are time dependent and reflect the institutional context of entrepreneurship. As illustrations, we investigate three historical episodes, ranging from the product led innovations of the industrial revolution, to the closely aligned innovations of the buyout wave of the 1980s to the more recent effects of finance led innovation. We identify systematic underlying factors that can cause significant differences in the entrepreneurial opportunity set. Managerial Summary : We provide lessons from three historical periods regarding how policy toward entrepreneurship might ensure technical and financial innovations are successfully intermediated. This implies an alliance‐based notion of entrepreneurship, underpinned by enabling systems of governance and suitable institutions reduced dependence on specific individuals or generations. A balance also should be struck to mitigate risky investment through sharing, and specifically equalizing rights and information between borrowers and lenders. Regulatory changes should discourage capital and information hoarding and support risky lending to asset‐backed, knowledge‐based industrial projects.